An experiment on a dynamic beauty contest game - Nobuyuki Hanaki; Yuta Takahashi (Osaka University, Institute of Social and Economic Research (ISER), 2023)
We present and conduct a novel experiment on a dynamic beauty contest game motivated by the canonical New-Keynesian model. Participants continuously provide forecasts for prices spanning multiple future periods. These forecasts determine the price for the current period and participants' payoffs. Our findings are threefold. First, the observed prices in the experiment deviate more from the rational expectations equilibrium prices under strategic complementarity than under strategic substitution. Second, participants' expectations respond to announcements of future shocks on average. Finally, participants employ heuristics in their forecasting; however, the choice of heuristic varies with the degree of strategic complementarity.
Keywords: C92; D84; E70; 330; Expectation formation; Learning-to-forecast experiment